Characterization of Bromodeoxyuridine-Induced Endogenous Guinea Pig Virus - Murray, Patrick R. (1974)
An endogenous virus (GPV) was induced after 5-bromodeoxyuridine treatment of cultured guinea pig cells. Compared to Gross murine leukemia virus (G-MuLV) GPV has a reproducibly heterogenous density of about 1.16 to 1.18 g/ml. The virion-associated RNA is slightly larger than that in G-MuLV. Sodium dodecyl sulfate-polyacrylamide gel electrophoretic analysis of dissociated GPV resolved five major structural proteins: I (molecular weight 70,000), II (molecular weight 36,000), III (molecular weight 24,000), IV (molecular weight 18,000), and V (molecular weight 16,000) which are similar to but distinct from G-MuLV proteins. Proteins I and II were demonstrated to be glycoproteins by incorporation of [(3)H]glucosamine. GPV and G-MuLV did not have any appreciable genetic homology or any common group-specific antigens when analyzed by immunodiffusion, radioimmunoassay, and indirect immunofluorescence. Morphogenesis of GPV also differed from that of a typical type C oncornavirus and proceeded via two pathways: (i) a majority of virus particles were formed in cytoplasmic vacuoles and were released after cellular disruption; and (ii) a minor population of particles were assembled in the cytoplasmic matrix and then migrated to the plasma membrane where they budded into the extracellular space. To date, GPV has been unable to initiate or maintain a productive replication in any cell line tested.